Life cycle assessment of coated abrasives and polishing agents : Case Mirka - Smedlund, Ida (My University, 2021)
This thesis presents and discusses the lifecycle assessment (LCA) of coated abrasives and polishing agents. The thesis was commissioned by Mirka Ltd. in 2020 and it’s aims are to 1) establish the environmental impact (as carbon and water footprints) of coated abrasives and polishing agents throughout the products’ life cycles and 2) compare the carbon footprint of three abrasives with the results from Henriksson’s 2012 thesis. The LCA methodology is standardised through the ISO 14040 and ISO 14044 standards and the number of LCA studies commissioned by companies is increasing. However, in the sanding solutions industry specifically are there yet not many published LCA studies. For this study the standardised LCA methodology was used, with background data from the ecoinvent 3.6 database and foreground data collected through Mirka employees. Data collected for the establishment of the environmental impact was made up of a sample of four PAPER, two PLASTIC, two NET and one TEXTILE coated abrasive products and four polishing agents. Data collected for the comparison included the products PRODUCT 1, PRODUCT 2 and PRODUCT 3. The data was assessed in the OpenLCA 1.10.2 software with the ReCiPe Midpoint (H) V1.13 method. The results show that one major contributor to the environmental impact is the raw material, followed by production for coated abrasives and packaging for polishing agents. The large impact of air freight is highlighted in the assessment of the distribution. The discussion on the end-of-life stage finds waste-to-energy (WtE) to be the most suitable option for the coated abrasives, with recycling or reuse the preferred option for the packaging materials. In the comparative assessment it is found that Mirka’s transition to WtE technology at the Jepua facility has zeroed the facility’s production impact. With the biggest environmental impact areas identified, Mirka can now search for solutions to lower their impact and have a benchmark to track their progress against.

Denna pro gradu avhandling presenterar och diskuterar livscykelanalysen (LCA) på sandpapper och polermedel. Avhandlingen som beställdes av Mirka Ltd. år 2020 har som mål att 1) etablera miljöpåverkan (koldioxid- och vattenfotavtryck) av sandpapper och polermedel under produkternas livscykel och 2) jämföra tre sandpappers koldioxidfotavtryck med resultaten från Henrikssons slutarbete från 2012. LCA metoden är standardiserad genom standarderna ISO 14040 och ISO 14044 och efterfrågan på LCA studier ökar bland företag. Inom slipmaterialsindustrin har det dock ännu inte publicerats någon större mängd LCA studier. I denna studie användes den standardiserade LCA metoden, med bakgrundsdata från ecoinvent 3.6 databasen och förgrundsdata som är insamlat i samarbete med anställda på Mirka. För etablering av produkternas miljöpåverkan samlades data ur ett stickprov på fem pappers- (PAPER), två plast- (PLASTIC) och två nätprodukter (NET), samt en textilprodukt (TEXTILE) ur sandpapperskategorin och fyra polermedel. Data för jämförelsen inkluderade produkterna PRODUCT 1, PRODUCT 2 och PRODUCT 3. Analysen gjordes i programvaran OpenLCA 1.10.2 med metoden ReCiPe Midpoint (H) V1.13. Enligt resultaten har råmaterialen den största inverkan på produkternas miljöpåverkan, med produktionen för sandpappren och förpackningsmaterialen för polermedlen på andra plats. Den höga påverkan av flygtransport synliggörs i analysen av distributionen. I diskussionen angående graven-delen av produkternas livscykel är slutsatsen att avfallsenergiprocesser är det bästa alternativet för sandpapper, medan återvinning eller återanvändning är att föredra för förpackningsmaterialen. I den jämförande delen synliggörs det att Mirkas övergång till avfallsförbränning som huvudsaklig energikälla vid fabriken i Jeppo har nollat fabrikens koldioxidfotavtryck för produktionen. När områden med den största miljöpåverkan nu identifierade kan Mirka hitta lösningar för att sänka deras påverkan och ha en baslinje att jämföra framstegen mot.
Keywords: carbon footprint; water footprint; life cycle analysis; environmental impact assessment; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management